PENGARUH PERTUMBUHAN LABA DAN LIKUIDITAS TERHADAP KUALITAS LABA PERUSAHAAN MANUFAKTUR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA 2017-2020 - Renil Septiano; Siti Aminah; Laynita Sari (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of earnings growth and liquidity on earnings quality in 2017-2020 companies (Study of Chemical and Basic Industrial Manufacturing Companies listed on the Indonesia Stock Exchange). This research uses quantitative research methods. The type of data used by the author is panel data. Sources of data that researchers use is secondary data. The secondary data that the researcher uses are in the form of financial statements of basic and chemical industrial manufacturing companies listed on the Indonesia Stock Exchange which are obtained through the links http://www.idx.co.id and http://idnfinancials.com and related websites. other. The population in this study are basic & chemical industrial manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020, totaling 78 companies. The sampling technique used in this article is purposive sampling with a total of 28 companies with 4 years and a total of 112 company data. Based on the results of the study, profit growth has no effect on quality, and liquidity has an effect on earnings quality. These results were obtained from the Eviws9 data processing.